Understanding Corporate Purpose: Bringing Clarity to Corporate Purpose, Success and Law - Mayer, Colin (Victoria University of Wellington Law Review, 2025)
We have misconceived the nature of the fundamental driver of a business, namely its profit. We do not account for its "true costs" and therefore do not report its "fair profits". Categorising this as a market failure arising from "externalities" has resulted in wrong policy prescriptions regarding competition and regulation to address the problem. Instead, we should recognise it as a failure to define the purpose of a business appropriately. Corporate law and corporate governance standards should establish that a profit derives from solving, not creating, problems for others. This is not a stakeholder theory of the firm. It retains the notion of "shareholder primacy" in corporate law, with the duties of directors remaining solely to their shareholders, but in the context of the success of the corporation deriving from profit without harm. The difference between the United Kingdom’s Companies Act 2006 and recent proposed changes to New Zealand’s Companies Act 1993 illustrates the reasons why broadening objectives of firms beyond shareholders to other stakeholders does not provide an appropriate resolution of the problem of internalising externalities. As Adam Smith noted in The Wealth of Nations, inclusion of profit without harm in law is central to freedom of choice of corporate purpose, the functioning of markets, the effects of competition and the ability of firms that incur their true costs to compete against those that do not.